Soldagem de estruturas pesadas de aço inoxidável ferrítico - Erika Braga Moreira (2009)
This study aimed to provide initial information about microstructure evolution and mechanical properties of 5 mm-thick UNS S43932 steel welded joints performed in typical conditions for heavy fabrication. Plates were produced in a steel maker using a tentative procedure to produce 5 mm-thick plates of ferritic stainless steel. The study involved the base material and the heat affected zone (HAZ) characterization afterwelding with a 430LNb cored wire. Microstructure and mechanical properties of the base material and of the HAZ obtained with four welding energy levels (from 0.4 to 1.2 kJ/mm) were studied. Welding thermal cycles in the HAZ were measured and used to help to characterize the weld microstructure. The results indicate that the base metalpresents an elevated grain size (around 410mm) demonstrating that this product processing procedure needs further development. Despite this elevated grain size, all tensile test specimens presented a ductile behavior. The same result was obtained in the welded joint tensile tests. On the other hand, the impact test results showed that both the base material and the HAZ presented low toughness. Fracture surfaceexamination indicated that this occurred by both clivage and intergranular fracture. Intergranular fracture surface was decorated by a large number of small precipitates.